Integrasi Augmented Reality dalam Festival Seni Budaya Berbasis Komunitas sebagai Model Pembelajaran dan Pelestarian Tari Tradisional Berkelanjutan - Elyakim Nova Supriyedi Patty; I Nyoman Yoga Sumadewa; Melati Rosanensi (CV. Global Cendekia Inti, 2026)
This study examined the integration of Augmented Reality in a community-based cultural festival as an innovative learning management model for preserving traditional dance and strengthening the local creative economy. The study was conducted in Sigar Penjalin Village, North Lombok Regency, where traditional art activities faced challenges such as low youth participation, limited promotion, and minimal use of digital technology. A mixed-methods approach with a design-based research framework was employed, involving stages of needs analysis, design, implementation, and evaluation. Data were collected through observation, interviews, questionnaires, and documentation. The findings indicated that the integration of Augmented Reality improved community participation, enhanced cultural understanding, and increased youth engagement in traditional arts. The program also supported the development of structured community-based learning activities and contributed to strengthening local cultural institutions. In addition, the study produced three Augmented Reality-based digital products as interactive learning and promotional media. This study proposed an integrative model combining technology, community-based learning management, and cultural activities that can be replicated in similar educational contexts.